On the Way to a Better Land Use Statistics - Meinel, Gotthard (Raumforschung und Raumordnung | Spatial Research and Planning, 2013)
Sustainable land use development requires a reporting system, which compares the actual development with the formulated goals and guiding principles of a sustainable land use policy. The current official land survey in Germany cannot longer meet the growing requirements on land use statistics regarding accuracy, reliability, timeliness, and relevance. Both, the use of cadastral data as primary data source of the statistical land survey, and also the sole computation of total areas of selected types of land use should be reviewed in this context. This paper highlights the problems of the database of current land use statistics, which are increasing significantly by technological changes of the cadastre. The benefits of using topographic geo-based data for the calculation are discussed. The monitor of the settlement and open space development (IÖR-Monitor) analysed this data and provides the indicator-based results in form of interactive maps and tables on the Internet. In addition, analysis of building structure and its change could be made based on real estate cadastre data. So land political sustainability goals as “inside before outside” would be verifiable. The contribution of this paper is to initiate a broad debate in this complex, interdisciplinary field between statistics, surveying, real estate management, geoinformatics and spatial development policy.
Keywords: Land use; Statistics; Official land survey; Indicators; Monitoring; Settlement development